Enhancing creative professional competence in foreign language acquisition for future environmental designers in Ukraine: a systematic review - Shayner, Hanna; Isayeva, Oksana; Mukan, Nataliya (Creativity Studies, 2026)
This comprehensive study investigates the development of creative professional competence in foreign language among students enrolled in Ukraine’s Environmental Design educational programmes. Drawing on survey data from 226 participants, the research highlights the growing recognition of the role of English language proficiency in equipping future environmental designers for global, interdisciplinary practice. The findings reveal that while a majority of students appreciate the importance of such competence, significant gaps remain in curriculum structure, resource accessibility, and instructional design. In particular, students report insufficient instructional hours and a lack of integration of authentic, profession-specific English materials – challenges that hinder the acquisition of specialized communicative skills. The study emphasizes that foreign language education must go beyond basic instruction and instead be embedded within real-world, design-related contexts. It advocates for the adoption of content and language integrated learning approaches, using debates, discussions, and design-based tasks to foster creativity, linguistic fluency, and intercultural competence. The dual use of English – both in scientific (designer-to-designer) and conversational (designer-to-client) registers – demands a curriculum that addresses both academic and practical communication needs. Therefore, the research calls for strategic reforms, including curriculum realignment, increased exposure to authentic materials, faculty training in English for specific purposes, and the integration of project-based and blended learning. Thus, creative professional competence in foreign language is not a supplementary skill but a foundational one – essential for enabling designers to express innovation, collaborate globally, and adapt in a dynamic professional landscape. Systemic institutional support may find benefit from to realize these educational goals and prepare designers for 21st century challenges.